The Effect of Occupational Health and Safety (OHS) and Motivation on Employee Performance at PT Lautan Sejahtera Nusantara - Damar Alam Pamungkas; Ghali Restu Munggaran; Herman Sofyandi (PT Mattawang Mediatama Solution, 2023)
human resources on the fact are Capital is one of the capital that plays an important role in achieving company goals. Motivation is a mental impulse that drives human behavior on the basis of need. Occupational safety is the control of people, machines, materials, and methods that cover the work environment so that workers do not experience injury. PT. LSN (Lautan Sejahtera Nusantara) is a company engaged in the marine and fisheries sector based on fishing activities. This research is a process that begins with a willingness or interest to know a particular problem which then develops into an idea, a theory from conceptualization. In general, there are three types of research, namely discovery, proof, and development. The research method used in this study is to use descriptive methods and quantitative methods. The descriptive method is used to describe, describe how the Occupational Health Safety, Motivation, and OHS Performance variables at PT. Lautan Sejahtera Nusantara already has good work motivation, the highest level of motivation is found in the employee factor helping colleagues when they have difficulty doing work, while the level of motivation the lowest factor is found in the Employee factor trying to increase mastery of skills to accelerate the process of achieving targets caused by tools and facilities that are inadequate and can hinder the development of employee skills. Employee performance in the company PT. Lautan Sejahtera Nusantara has a significant influence on employee performance based on perceptions acquired by employees